Effect of classmate as peer-led education on clinical performance: A mixed-method study - Roghayeh Mehdipour-Rabori; Monirsadat Nematollahi; Behnaz Bagherian (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Achieving an excellent clinical education by nursing students is one of the primary goals of any nursing school. Nursing educators try to use different methods to enhance clinical skills. One of them is a peer-led method that can be used in theoretical and clinical education. It is developing as a suitable educational method to promote health. This study assessed the effect of classmates as peer-led education on the clinical performance of nursing students. MATERIALS AND METHODS: This study was conducted using a mixed-method approach and a sequential explanatory design. In the quantitative phase, a quasi-experimental study with a two-group pre- and post-test design was conducted. The sample of this phase consisted of 70 nursing students (35 persons in each group) who were selected through random convenience sampling. The intervention group participated in a peer-led education program. The control group received routine training. The members of both groups completed the clinical performance checklist before, and after the intervention, The collected data were analyzed using SPSS V21 software using descriptive and inferential statistics. In the qualitative phase, the researchers interviewed 18 undergraduate students using semi-structured in-depth and face-to-face approaches. These participants were selected by purposive sampling method. Data were analyzed using conventional content analysis. MAX DATA 10 was used to categorize the data. To establish the reliability and validity of findings, Graneheim, and Landman's criteria were considered RESULTS: In the quantitative phase of the study, the results showed that the mean score of clinical performance was not statistically significant between the control and intervention groups before the intervention (P > 0.05). At the same time, it was significantly different after the intervention (P < 0.05), implying that the peer-led education of the intervention group significantly increased compared to that of the control. The main theme was "learning based on friendship," which included two categories, namely "deep learning" and "learn in the shadow of relaxing." CONCLUSION: Classmate as peer-led education could increase the ability of nursing students in clinical performance, and was able to enhance deep learning among them.